Levels and Health Risk Assessments of Heavy Metals in Khat and Its Support Soil in Algesachi, Ilu Ababor, Ethiopia - Shibiru Damana; Abiyot Kelecha Geletu; Ibrahim Umer Keru (SAGE Publishing, 2024)
Background: Khat ( Catha edulis Forsk ) is a stimulant plant grown in East Africa and the Arabian Peninsula. Heavy metal pollution has been a global concern due to its acute and chronic health effects and the major route of exposure is the consumption of contaminated foods. In this study, the determination and health risk assessment of heavy metals (Mn, Cu, Zn, Ni, Cr, Cd, and Pb) in khat and its support soil samples was carried out. Materials and Methods: Khat and its support soil were analyzed for the levels of 7 toxic heavy metals by Atomic Absorption Spectrophotometer. Samples were randomly collected from 3 districts of khat farming kebeles and digested using mixture of strong acids. Results: The concentrations (mg/kg) of analytes in soil and khat samples were: Cu (6.78-35.80); Zn (24.30-199.02); Mn (7.59-1855.40); Ni (6.37-64.80); Cr (0.82-169.20); Cd (14.2-38.8), and Pb (ND). Among the analyzed heavy metals in soil, Mn was with the highest concentration, followed by Zn, Cr, Cu, Ni, and Cd while that of Zn was the maximum followed by Cu, Mn, and Cr in khat. The levels of Zn, Cr, and Cd in soil samples from all study sites and detected concentrations of Cr in khat samples exceeded the recommended FAO/WHO levels. Conclusion: The hazard index (HI) of metals in khat from study areas was less than 1 indicating a less likelihood of non-carcinogenic toxicological health effects. However, the presence of these toxic chemicals in soil and khat indicates product contamination and needs extensive further investigation involving other heavy metals.